Adsorption of associating fluids at active surfaces: a density functional theory - Tripathi, S.; Chapman, W.G. (Condensed Matter Physics, 2003)
We present a density functional theory (DFT) to describe adsorption in systems
where molecules of associating fluids can bond (or associate) with
discrete, localized functional groups attached to the surfaces, in addition to
other fluid molecules. For such systems as water adsorbing on activated
carbon, silica, clay minerals etc. this is a realistic model to account for surface
heterogeneity rather than using a continuous smeared surface-fluid
potential employed in most of the theoretical works on adsorption on heterogeneous
surfaces. Association is modelled within the framework of first
order thermodynamic perturbation theory (TPT1). The new theory accurately
predicts the distribution of bonded and non-bonded species and adsorption
behavior under various conditions of bulk pressure, surface-fluid
and fluid-fluid association strengths. Competition between the surface-fluid
and fluid-fluid association is analyzed for fluids with multiple association
sites and its impact on adsorption is discussed. The theory, supported by
simulations demonstrates that the extent and the nature of adsorption (e.g.
monolayer) vary with the number of association sites on the fluid molecules Ми застосовуємо теорію функціоналу густини (ТФГ) до опису систем, у яких молекули асоціативних плинів можуть зв’язуватися (або
асоціювати) з дискретними локалізованими функціональними групами, приєднаними до поверхонь, на додаток до інших молекул
флюїду. Для таких систем як вода, що адсорбується на активованому вуглеці, кремнії, глині, це є реалістичнішою моделлю для врахування поверхневої неоднорідності, ніж використання неперервного
липкого потенціалу поверхня-плин, що застосовується в більшості
теоретичних робіт з адсорбції на неоднорідних поверхнях. Асоціація
моделюється в межах першого порядку термодинамічної теорії збурень (ТТЗ1). Нова теорія дає точне передбачення розподілу зв’язаних і незв’язаних зразків і адсорбційної поведінки при різних значеннях об’ємного тиску і асоціативної взаємодії поверхня-плин і плин-плин. Проведено порівняльний аналіз між асоціативною взаємодією
поверхня-плин і плин-плин для флюїдів зі складними асоціативними
вузлами і обговорено їх вплив на адсорбцію. Теорія, підкріплена симуляціями, показує, що міра і природа адсорбції змінюється зі зміною кількості вузлів асоціації на молекулах флюїду.